(untitled) (Nigerian Journal of Physiological Sciences, 2024)
Polycystic ovary syndrome (PCOS) is characterized by hyperandrogenemia, irregular menstrual cycle, and small cysts on the ovaries. This condition can be morphological or biochemical (elevated testosterone). Elevated testosterone (hyperandrogenemia) is the hallmark of PCOS, which can inhibit follicular development, anovulation, or cause irregular menstrual changes. Unfortunately, there is no cure for PCOS, and available treatment options are restricted to mitigating its symptoms. This study was, however, designed to investigate the synergistic effect of clomiphene (CLO) and carvedilol (CAL) on PCOS-induced female infertility. Thirty female Wistar rats were randomized into 5 groups (n= 6/group) control, PCOS, PCOS+ CLO, PCOS+CAL, and PCOS+ CLO+CAL. The administration was once daily via the oral route and lasted for 15 days. Clomiphene and carvedilol synergistically ameliorated PCOS-induced elevated serum gonadotropin-releasing hormone, luteinizing hormone (LH), testosterone and prolactin, and decreased follicle stimulating hormone (FSH), estrogen and progesterone. This was accompanied by the downregulation of PCOS-induced overexpression of ovarian LH, androgen, and FSH receptors. It was also accompanied by a decrease in inflammatory markers such as ovarian interleukin 1 beta and Nuclear factor kappa B (NF-κB) and apoptosis markers such as ovarian caspase 3 and an increase in ovarian Nuclear factor erythroid-2-related factor 2 (Nrf2), Heme Oxygenase 1 (HO 1 or HMO-1), catalase and glutathione reductase. This study shows that carvedilol and clomiphene combination therapy alleviates inflammation and redox imbalance in experimental PCOS.